Quality of life in parents of childhood leukemia survivors. A French Childhood Cancer Survivor Study for Leukemia study. Issue 10 (15th August 2020) - Vercasson, Camille; Auquier, Pascal; Michel, Gérard; Bertrand, Yves; Ansoborlo, Sophie; Tabone, Marie‐Dominique; Leverger, Guy; Gandemer, Virginie; Baruchel, André; Contet, Audrey; Dalle, Jean‐Hugues; Paillard, Catherine; et al.
Abstract: Introduction: Our objectives were to assess the quality of life (QoL) of parents of childhood leukemia survivors compared with population norms and to identify the determinants of parents' long‐term QoL. Methods: Parents of minors who had survived childhood leukemia participating in the French LEA cohort (Leucémie de l'Enfant et de l'Adolescent—French Childhood Cancer Survivor Study for Leukemia) were asked to complete the French version of the WHOQOL‐BREF. Results were compared with age‐ and sex‐matched values from a French reference population. Parents' and survivors' characteristics likely to be associated with QoL, long after the child's leukemia diagnosis, were explored using multivariate analysis. Results: We included 487 parents (mean age 42.9 ± 6.0 years, mean follow‐up time from diagnosis 7.3 ± 3.3 years). Compared with the reference population, scores for physical health and social relationships for parents of childhood leukemia survivors were significantly lower ( P  < 0.001, effect size = 0.24 and P  < 0.001, effect size = 0.29, respectively) contrary to scores for psychological health which were significantly higher ( P  < 0.001, effect size = 0.29). Even if health‐ and cancer‐related characteristics were associated with parents' QoL in some dimensions, the only factor associated with each of the three dimensions (social relationships, physical health, and psychological) in the multivariate analysis was the parent's financial situation. Conclusions: Long after leukemia diagnosis, the parents reported lower scores in the physical health and social relationship domains. Despite the difficulties of actually influencing socioeconomic characteristics, it is important to consider the social situation of each family in the long‐term care of survivors and their families.